Harmonizovaná FMEA analýza - Riabov, Mikhail (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2022)
Cílem diplomové práce na téma “Harmonizovaná FMEA analýza“ je seznámit se s principy plánování kvality a nastudovat teorii o existujících nástrojích APQP, nastudovat novou příručkou harmonizované FMEA analýzy a dostupnými SW nástroji pro podporu projektu. Daná práce se zaměří hlavně na DFMEA analýzu trakční sestavy, bude popsán koncept přechodu na novou harmonizovanou verzi VDA/AIAG, která splňuje požadavky na jasný a srozumitelný výstup, požadovaný výrobcem, dodavatelem i zákazníkem. Diplomová práce je zpracována jako podrobný srozumitelný návod pro snadnější zpracování FMEA analýzy podle nové příručky.

The target of the diploma thesis on „Harmonized FMEA analysis“ is to familiarize with principles of quality planning and studying the theory of existing APQP tools. Another goal is to learn the basics of the new manual of harmonized FMEA analysis and discover some available SW tools for project support. This diploma thesis will be focused mainly on DFMEA analysis of traction assembly and the concept of changing to new harmonized version from VDA/AIAG will be explained. This concept meets the requirements for clear and comprehensible output required by the manufacturer, supplier, and customer. The diploma thesis is elaborated as a detailed clear guide for easier processing of FMEA according to the new manual.
Harmonized FMEA analysis
Keywords: Kvalita; plánování; FMEA analýza; technická rizika; metody kvality; vady; VDA; AIAG; metodika; odhalitelnost; harmonizace.; Quality; planning; FMEA analysis; technical risks; quality methods; defects; VDA; AIAG; methodology; detectability; harmonization.